Peer PrEP referral + HIV self-test delivery for PrEP initiation among young Kenyan women: study protocol for a hybrid cluster-randomized controlled trial - Wairimu, Njeri; Malen, Rachel C.; Reedy, Adriana M.; Mogere, Peter; Njeru, Irene; Culquichicón, Carlos; McGowan, Maureen; Gao, Fei; Baeten, Jared M.; Ngure, Kenneth; Ortblad, Katrina (Trials, 2023)
Oral HIV pre-exposure prophylaxis (PrEP) for HIV prevention is highly effective, but uptake remains low in Africa, especially among young women who are a priority population for HIV prevention services. HIV self-testing (HIVST) has been proven to increase HIV testing in diverse populations but has been underutilized to support linkage to HIV prevention services. Most young women who initiate PrEP in Africa do so through informal peer referral. We wanted to test a model of formalized peer referral enhanced with HIVST delivery among young Kenyan women.